Increased Demand of Emergency Medical Services in Covid-19 - Vaibhav Vikas Bisne (Institute of Medico-legal Publications Pvt Ltd, 2021)
The World is going through a tough situation and that is a pandemic caused by the Novel Corona virus whichoriginated in the Wuhan Province of China in December 2019. During this tough and critical situation, theonly saviors of humanity are our health care professionals, who restore the faith and trust in humanity andensure the safety of each individual suffering from this COVID-19 disease. The cherry on the cake is theadditional health support provided by the staff of Emergency Medical Services who help the health careworkers in treating the patients in hospital, by giving the pre-requisite or the initial treatment during thisemergency situation. So to tackle this pandemic, it is important to meet up to the increasing demand ofEmergency Medical Services so that the situation remains under control and there is a decrease in mortality.The fragile and fragmented healthcare system of India needs to be upgraded and emphasis needs to be puton developing the Em